Perbandingan Struktur Modal dan Nilai Perusahaan Sebelum dan Saat Pandemi Covid-19 di Bursa Efek Indonesia - Devita Asri; Abdul Basyith; Ummi Kalsum (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The purpose of this study is to know the structure of capital and value companies before and when the covid-19 pandemic in the Indonesian stock exchange. This study includes association research. There are six variables used, which are capital structures, profitability, liquidity, corporate sizes, and dummy variables. The study's population is the health, telecommunications, and tourism Sub Company registered in the Indonesia Stock Exchange in 2018-2021. The sample in this study represents 23 companies. The data used is secondary data. Data collection techniques are documenting. The analysis techniques used are descryptive, electronic regression dummy statistics, multicolicerity tests, autokolinerity tests, heteroocrity tests, modeling verification tests, regression coefficient tests, and deterministic coefficients. Research has shown 1) profitability, liquidity, corporate size, and dummy variables have significantly affected the capital structure before and when the covid-19 pandemic. 2) capital structures, profitability, liquidity, corporate sizes, and dummy variables have significantly affected the company's values before and during the covid-19 pandemic.